Les entreprises en économie sociale face aux défis de l’hybridation des ressources - Laurent Sauvage; Nathalie Lachapelle; Diane-Gabrielle Tremblay (Revue Interventions Économiques)
This article analyzes the resources, market and non market and non-financial, which are used by Québec social economy firms. This diversification of resources leads firms to respond to demands from the market and from the persons who are the object of their social missions, and these are sometimes contradictory. Firms often need to be very adaptable to reduce the tensions associated with the various logics (market, administrative and social). The hybridization of resources can be a response to these tensions and social firms can develop strategies in order to remain independent from the various funding sources, particularly the State.Keywords: social firms, social economy, management, governance, hybridization